Asset Price Shock Response to Shock Capital Flow, Exchange Rate, and Interest Rate: Case Study of 16 Emerging Market Countries - guswardi, rachman (Universitas Airlangga, 2016)
Capital flows to developing countries and emerging markets in the world is constantly increasing. However, the crisis that occurred in 2008 and 2011 caused concern for investors. A series of policies have been carried out in several emerging market countries to take steps prudence in controlling capital flows. This study aimed to analyze the response of asset prices to the shock caused by capital inflows, interest rates and exchange rates and analyzes the contribution of shock in capital inflows, interest rates and exchange rates on asset prices in 16 emerging market countries (India, Brazil, Russia, Indonesia, Republic of South Africa, Mexico, Thailand, South Korea, Colombia, Philippines, Egypt, Hong Kong, Peru, Czech, Bangladesh, Hungary) in the year 2001-2015. The method used is quantitative method using Panel Vector Auto Regression models. The results of this study show that the first shock of positive capital inflows will affect asset prices, both that a positive shock on interest rates will affect asset prices, the third that the positive shock of the exchange rate would affect asset prices. The variables that have the biggest contribution in influencing asset prices is the exchange rate which further interest rates and the smallest is the capital inflows Keywords: Capital Inflows, Exchange Rate, Interest Rate, Asset Prices, Emerging Market, Panel Vector Auto Regression.JEL: G12